Lymphocyte‐to‐Monocyte Ratio Is a Predictor of Survival After Liver Transplantation for Hepatocellular Carcinoma. Issue 11 (8th November 2018) - Mano, Yohei; Yoshizumi, Tomoharu; Yugawa, Kyohei; Ohira, Masafumi; Motomura, Takashi; Toshima, Takeo; Itoh, Shinji; Harada, Noboru; Ikegami, Toru; Soejima, Yuji; Maehara, Yoshihiko
Abstract : Recent studies revealed that systemic inflammation was correlated with poorer prognosis in various cancers. We investigated the prognostic value of the lymphocyte‐to‐monocyte ratio (LMR) in patients who underwent living donor liver transplantation (LDLT) for hepatocellular carcinoma (HCC). We retrospectively analyzed the records of 216 patients who underwent LDLT for HCC. Patients were divided into high (n = 126) and low (n = 90) LMR groups. Their clinicopathological parameters and survival times were compared. To determine the mechanisms of the change in the LMR, we performed immunohistochemical analyses of CD3 and CD68 expression. A low LMR was significantly associated with a high Model for End‐Stage Liver Disease score; a high Child‐Pugh score; elevation of alpha‐fetoprotein, des‐gamma‐carboxyprothrombin, and neutrophil‐to‐lymphocyte ratio; larger tumor size; more tumors; and poorer prognosis. A low LMR was associated with poor prognosis and represented an independent prognostic factor, particularly among patients beyond the Milan criteria. The ratio of CD3‐positive to CD68‐positive cells was significantly lower in the low‐LMR group. In conclusion, our results show that the LMR was an independent predictor of survival of patients with HCC beyond the Milan criteria who underwent LDLT. The LMR reflected the immune status of the tumor microenvironment.